THE IMPACT OF VITAMIN A, D, AND B-COMPLEX DEFICIENCY ON COGNITIVE DEVELOPMENT IN CHILDREN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Micronutrients and vitamins are key biological determinants in shaping children’s health and intellectual potential. In particular, deficiency of vitamins A, D, and B group (hypovitaminosis) adversely affects central nervous system development, neurocognitive functions, memory, attention, and learning abilities. According to data from the World Health Organization (WHO), 30–40% of children under five years of age in developing countries are affected by varying degrees of vitamin deficiency. This review of scientific literature aims to analyze the mechanisms by which hypovitaminosis of vitamins A, D, and B group influences cognitive development in children from epidemiological, clinical, and neurobiological perspectives. The article synthesizes findings from recent meta-analyses, cohort studies, and randomized clinical trials.